Analysis Strategy Financing Payment Problems In The System Murabahah: A Case Study Bmt Kube Bandar Setia Sejahtera 001 Percut Sei Tuan - Siti Mujiatun; Hafidz Hafidz (Proceeding International Seminar of Islamic Studies, 2019)
Bank Indonesia as the central bank and banking supervisor in Indonesia has determined the size of the assessment of the well-grounded of banks. One of the qualifications of BI is that banks with problematic payments must not exceed 5% ( Jurnal JEST,Vol.1;2014). Preliminary data obtained in the field indicate that problematic payments at BMT KUBE Sejahtera 001 Bandar Setia are more than 10%, and this is a matter of research that must be carried out. This research is a qualitative study using three data sources; literature, interviews and observations. The results of the study were obtained that (1). The factors that cause problematic payments at BMT KUBE Sejahtera 001 Bandar Setia are (a) Weak purchasing power (60%); (b) Number of similar trade competition (30%); (c) The customer changed address and did not report to BMT KUBE Sejahtera 001 Bandar Setia (10%). (2). The strategies were implemented by BMT KUBE Sejahtera 001 Bandar Setia in handling problem payments on murabahah financing were: (a). Providing warning letters to BMT members who experience problem payments. (b). BMT KUBE Sejahtera 001 Bandar Setia made a visit to the homes of BMT members who experienced problematic payments to see the objective conditions of the members and the business being run. (c). BMT KUBE Sejahtera 001 Bandar Setia asked directly about the business development of BMT members who experienced problems in repaying loans. (d). BMT KUBE Sejahtera 001 Bandar Setia reschedules problem financing.